Acoustic Analysis on Cleft Lip Speech Signal - Sitti Agripina Alodia Yusuf; Nani Sulistianingsih; Muhammad Imam Dinata; Syahroni Hidayat; Joelianto Darmawan (Sekawan Institut, 2025)
Cleft conditions significantly disrupt phonetic articulation, leading to hypernasality and irregular resonance characteristics. In this study, the formant analysis of normal and cleft speech is presented, with the aim of investigating acoustic differences in formant frequencies between cleft and normal speech using real-word utterances, focusing on the articulation of plosive consonants and resonance variability. The dataset consisted of 280 speech signals (140 cleft and 140 normal) uttering word /paku/. The speech signals were resampled to 16kHz and the silence in the speech was removed, next stage was followed by extracting the first three formants using the Burg algorithm. Statistical analysis revealed that the value of F1 and F2 in cleft speech were higher, alongside greater variability in formant distribution. Further analysis of plosive articulation highlighted irregular formant transition in cleft speech, indicating compromised intraoral pressure control. Additionally, a moderate negative correlation (r = -0.423, p<0.001) between F1 and F3 suggests a spectral pattern indicative of hypernasality. This finding underscores the potential of formant-based acoustic features as objective markers for early clinical assessment and provides a foundation for the development of diagnostic models in cleft speech research.